Effect of processing on the sensory profile and constituents of volatile acerola juice - Lilian Geovania Costa Pinto (2007)
In the present work the changes in the sensorial profile and the volatile profile of acerola plain juice due to industrial processing were monitored. Initially it was determined the volatile composition of the in natura acerola juice and the main odor-active compounds were assessed by the Osme CG-olfactometry technique. Later, five steps of juice processing were sampled: extraction, finishing, centrifugation, thermal treatment, final product with chemical preservatives. These samples were submitted to chromatographic and sensory analyses. Volatile compounds were isolated by using a dynamic headspace technique by suction, in Porapak Q, analyzed by high resolution gas chromatography (FID) and identified by GC-MS. 92 compounds were detected in the headspace of acerola juice, from which 56 were identified and 6 were tentatively identified. The olfactometric analysis was able to detect 79 odoriferous compounds, from which 27 were considered the most important contributors to the characteristic acerola aroma. These compounds were classified in three groups: âcompounds with acerola aromaâ (Group 1) as hexanal, ethyl butanoate e E-3-hexen-1-ol; âcompounds described as pleasant notesâ (Group 2), like Z-3-hexenal, Z-3-hexen-1-ol, 4-pentenyl acetate, methyl hexanoate and ethyl hexanoate; âcompounds described as unpleasant notesâ (Group 3), like 1-octen-3-ol, 3-octanol and Z-3-hexenyl acetate. The mentioned compounds were the ones that showed the highest aroma intensities and were chosen to be monitored. In the first group, the compounds hexanal and ethyl butanoate showed good stability, while E-3-hexen-1-ol was drastically reduced with the thermal treatment. In Group 2, Z-3-hexenal and Z-3-hexen-1-ol also suffered great damages during the heating step. Compounds 1-octen-3-l and 3-octanol from Group 3 were totally lost when the food preservatives were added. By means of Quantitative Descriptive Analysis, it was observed that the samples from the beginning steps (extraction, finishing and centrifugation) showed similar sensory profiles, and were characterized by high intensities of acerola aroma, acerola flavor, green acerola aroma, green acerola flavor, which had been diminishing throughout the processing. The final steps (thermal treatment and preservatives addition) were the ones which provoked the greater changes in the acerola juice sensory profile, increasing the artificial aroma and flavor perception. A positive correlation was determined between E-3-hexen-1-ol and acerola flavor. The descriptor acerola aroma correlated negatively to 4-pentenyl-acetate and methyl hexanoate. Compounds ethyl hexanoate and methyl hexanoate showed positive correlation to artificial aroma and artificial flavor, respectively, while Z-3-hexenyl acetate was directly proportional to the intensity of both descriptors. The cooked aroma descriptor was positively correlated to methyl hexanoate and 4-pentenyl acetate and negatively correlated to 1-octen-3-ol. Compounds ethyl butanoate and 3-octanol showed no significant correlation to any sensory descriptor.